Hypophosphatasia: Biological and Clinical Aspects, Avenues for Therapy - Salles, Jean Pierre (Clin Biochem Rev, 2020)
Hypophosphatasia (HPP) is a rare inherited systemic metabolic disease caused by mutations in the tissue-nonspecific alkaline phosphatase (TNSALP) gene. TNSALP is expressed in the liver, kidney and bone, and its substrates include TNSALP inorganic pyrophosphate, pyridoxal-5′-phosphate (PLP)/vitamin B6 and phosphoethanolamine (PEA). Autosomal recessive and dominant forms of the disease result in a range of clinical entities. Major hallmarks are low alkaline phosphatase (ALP) and elevated PLP and PEA levels. Very severe infantile forms of HPP cause premature death as a result of respiratory insufficiency and also present with hypo-mineralisation leading to deformed limbs with, in some cases, the near-absence of bones and skull altogether. Respiratory failure, rib fractures and seizures due to vitamin B6 deficiency are indicative of a poor prognosis. Craniosynostosis is frequent. HPP leads to an unusual presentation of rickets with high levels of calcium and phosphorus, resulting in hypercalciuria, nephrocalcinosis and low ALP levels. Hypercalcaemic crisis, failure to thrive and growth retardation are concerns in infants. Fractures are common in both infantile and adult forms of the disease, concomitantly occurring with unexplained chronic pain and fatigue. Dental clinical presentations, which include the premature loss of teeth, are also commonly found in HPP and specifically manifest as odontohypophosphatasia. A novel enzyme therapy for human HPP, asfotase alfa, which is specifically targeted to mineralised tissues, has been developed in the past decades. While this treatment seems very promising, especially for infantile HPP, many questions regarding its long-term effects, the management of treatment, and any potential secondary adverse effects remain unresolved.